Impact of conductivity on Lorentzian and Fano resonant high-Q THz metamaterials: Superconductor, metal and perfect electric conductor - Srivastava, Yogesh Kumar (2017)
High temperature superconductors have created exciting opportunities for switchable metamaterial and plasmonic devices operating at terahertz frequencies. In recent times, there have been several demonstrations using superconducting metamaterials, such as thermal, electrical, magnetic, and optical switching. Here, we explore the impact of conductivity on terahertz metamaterial resonators with different resonance line shapes. Lorentzian and Fano line shaped resonators show different levels of enhancement in the quality factor and resonance intensity for metallic, superconductor, and perfect electric conductors, due to the interplay between the radiative and the non-radiative loss mechanisms in a metamaterial array.